Aplikasi Sistem Informasi Geografi (SIG) untuk Kajian Fluktuasi Muka Air Tanah dan Karakteristik Akuifer di Kecamatan Denpasar Utara, Kota Denpasar - I GUSTI AYU ADE TEJASTINI; I WAYAN DIARA; I NYOMAN DIBIA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Aplication Geographic Informastion System (GIS) for Study of Ground Water Fluctuations and Characteristics of Aquifers in the District of North Denpasar, Denpasar City The use of water in everyday life is very influential on the pattern of water use available. Ground water is water located on rock is layer below the water is surface. The study was conducted in North Denpasar District, Denpasar City from November 2018 to March 2019. The method used is a survey method, purposive sampling method and descriptive quantitative. The results of the study is ground water fluctuations are ??between 0 m - 5 m and 5 m - 10 m. Distribution of the depth of the ground water in the North Denpasar District which varied greatly in the dry season between 4,5 m – 22,1 m and in the rainy season between 5,1 m – 21,6 m. Ground water fluctuations in the study area are ??between 0 m - 5 m and 5 m - 10 m. The direction of ground water flow in North Denpasar District is predicted flowing to west, south west and to south but leaning more to the southwest. Characteristics of aquifers in North Denpasar District is classified as good aquifers with rock constituent material consisting of sand tuff, sandstone and clay sand which can potentially store and drain water.